Mathematical foundations of fuzzy sets - Wu, Hsien-Chung (John Wiley & Sons, Inc., 2023)
"Mathematical Foundation of Fuzzy Sets addresses both GRS and GMSE, although with a much stronger emphasis on the former. For completeness, this book begins with a review of shear strength of soils and classical earth pressure theories. The load-deformation behaviour of GRS mass as a composite, reinforcing mechanisms of GRS, and GRS walls with different types of facing, are then covered, followed by the use of geosynthetics as reinforcement. Design concepts with examples are also fully covered, as is the construction of GRS walls, including construction procedures and general construction guidelines."--